O ensino da língua brasileira de sinais - Libras - a ouvintes pela perspectiva da abordagem intercultural - Lopes, Antonia Aparecida (2022)
Research about Brazilian Sign Language – Libras –, used by Deaf people in Brazil, has begun to advance due to its recognition as a legal mean of communication and expression by Deaf people through Law No.10.436, dated April 24th, 2002, regulated by Decree 5626/2005. However, most studies are focused on language acquisition by Deaf people, with a low number of research projects focusing on teaching Libras to hearing people. For this reason, this research seeks to answer the following question: Considering the intercultural approach, what are its didactic-methodological contributions for teaching Libras to beginners hearing adults? Our objective, considering this research question, is to investigate the didactic-methodological contributions of the intercultural approach for teaching Libras to hearing people that are fluent in Portuguese. As our specific objectives we seek to: i) discuss concepts and approaches to language teaching, especially the intercultural approach; ii) identify the main didactic-methodological aspects in publications about teaching Libras to hearing people that are fluent in Portuguese; and iii) propose didactic-methodological insights for teaching Libras to beginners hearing adults that are fluent in Portuguese, using an intercultural approach. Our research is based upon an interpretive analysis, having Applied Linguistics, Intercultural Approach and Libras as the theoretical basis. It is characterized as a research conducted using a qualitative approach, and with an exploratory character, using as our data generation instruments the bibliographical research and the analysis of bibliographical materials, in order to identify the main didactic-methodological aspects in publications about teaching Libras to hearing people that are fluent in Portuguese. Our data were generated, analyzed and examined using Applied Linguistics references, and thus our analysis indicated that there is scarcity of studies using the intercultural approach to teach Libras to hearing people that are fluent in Portuguese. Considering the didactic-methodological insights, we have offered eight teaching activities to Libras’ teachers, in accordance with the theoretical foundations of the intercultural approach, inspired on teaching techniques presented by Janowska (2020), enabling the hearing adults that are studying Libras and that are fluent in Portuguese to develop their intercultural competences.